Answer:
The actual answer is 7/2
Step-by-step explanation:
Answer:
2
Step-by-step explanation:
Substitute a = - 6 into the expression, that is
a² + 7a + 8
= (- 6)² + 7(- 6) + 8 = 36 - 42 + 8 = - 6 + 8 = 2
None of the above
My mom just helped me with it, so I don't know if it's exactly alright. She said it was 20, but theres no 20 as I checked, and I don't know if she didn't right. I got a whole 25.
ANSWERS I THINK
_______________
I think its mainly a,e, or b. Mainly b?
Answer:
addition
Step-by-step explanation:
The given expression is ![(8-2x)^2+4](https://tex.z-dn.net/?f=%288-2x%29%5E2%2B4)
We want to determine the last operation performed when evaluating this expression for x=3.
We substitute to get:
![(8-2*3)^2+4](https://tex.z-dn.net/?f=%288-2%2A3%29%5E2%2B4)
Multiply within the parenthesis to get:
![(8-6)^2+4](https://tex.z-dn.net/?f=%288-6%29%5E2%2B4)
Subtract to get:
![2^2+4](https://tex.z-dn.net/?f=2%5E2%2B4)
Evaluate the exponent to get:
4+4
Add to obtain:
8
Hence the final operation is addition
Answer:
1/6 ,1/6, 1/24, no events A and B are not independent events.
Step-by-step explanation: